A phase I, randomized study to evaluate the safety, tolerability, and pharmacokinetics of mefunidone in healthy subjects - Han, Mai; Huo, Bishan; Hu, Gaoyun; Zhang, Xin; Cui, Gang; Wu, Wei; Mi, Na; Zhang, Shixi; Jin, Jiangli; Lu, Xing; Wu, Bidong; Xiao, Chunyan; et al. (Frontiers in Pharmacology, 2024)
Background: Mefunidone is a novel synthetic compound and an improvement over pirfenidone for the anti-fibrotic treatment of renal fibrosis in end-stage renal disease. We conducted this first-in-human, phase I clinical trial to determine the safety, tolerability, and pharmacokinetic (including food effect) profiles of mefunidone administered orally as single and multiple ascending doses in healthy subjects. Methods: Part A assessed single ascending doses of mefunidone from 25 mg to 800 mg or placebo once daily in the fasted state. Part A also assessed the effect of food on the tolerability and PK in cohort 100 mg. Part B consisted of 3 treatment groups who received 100 mg, 200 mg or 400 mg of mefunidone or placebo twice daily (BID, bis in die) on Days 1-6, and once in the morning on Day 7. Results: Single oral doses of mefunidone up to 800 mg and multiple doses of mefunidone up to 400 mg BID were all well tolerated. Mefunidone behaved along with ideal dose proportionality within single dose range of 50 mg to 600 mg and multiple dose range of 100 mg BID to 400 mg BID by Day 7. High-fat fed conditions led to a delay in Tmax about 1 hour and a slight reduction of about 20% in Cmax compared to fasted conditions, but didn't significantly affect the systemic exposure. Conclusions: Mefunidone exhibited favorable pharmacokinetics and safety profiles. The present study informed and supported further development clinical study of mefunidone.